Pengaruh Nilai Hedonis, Reputasi Merek, dan Informasi Dari Mulut Ke Mulut Terhadap Niat Beli Pada Produk Starbucks Di Surabaya - Kamaluddin, Ahmad; Rachmat, Basuki; Ronny, Ronny; Nurhadi, Mochamad (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This research aims to analyze and identify the influence of Hedonic Value, Brand Reputation, and Information from Word of Mouth on Purchase Intentions for Starbucks Products in Surabaya. The research was conducted on Starbucks Customers or Consumers in Surabaya with a total sample of 100 people. Data collection techniques used were questionnaires via Google forms and conventional ones directly. Variable measurement uses a Likert scale with a scale of 1-7 and analysis for data processing uses the Multiple Linear Regression Analysis method using SPSS Ver.26 software. The research results show that Hedonic Value, Brand Reputation, and Information from Word of Mouth have a significant positive effect on Purchase Intention.